EXPERTISE, INDEPENDENCE AND PROFESSIONAL SKILLS OF INTERNAL AUDITORS IN PREVENTING FRAUD ON E-COMMERCE TRANSACTIONS (A CASE STUDY AT PT KERETA API INDONESIA) - Arsy Eza Febie Romadhina (Association of Certified Fraud Examiners Indonesia Chapter, 2016)
Nowadays, the development of information technology has given significant impact on various activities. Easy facilities provided by information technology enable the society, especially costumers, to make transactions at their workplace or home. Such demands make producers and companies feel the need to apply e-commerce their business. This research aims to give information about the expertise, independence, and professional skill of the internal auditors in preventing fraud on e-commerce transactions. This research applies Miles and Huberman model with three activities in the data analysis, such as: data reduction, data model, and conclusion withdrawal. This research uses qualitative research with a case study at PT KeretaApi Indonesia (Persero). The result obtained from this research shows that the audit process of e-commerce at PT KeretaApi Indonesia (Persero) is entirely conducted by the Internal Auditors in IT Unit, because IT Unit has its own Team of Auditors outside the SPI Unit (Internal Auditor Unit) of PT KeretaApi Indonesia (Persero).